Key components of enhanced recovery after surgery protocol in lung cancer surgery - A. K. Каchur; V. K. Lyadov (Исследования и практика в медицине, 2021)
Due to the high lung cancer morbidity and the need for surgical intervention in that patient population, introduction of the concept of standard protocol for enhanced recovery after surgery (ERAS) may lead to a significant decrease of the rate of postoperative complications and hospital stay. The aim of the review was to assess the main components of ERAS protocol in thoracic cancer surgery using video-assisted thoracoscopic interventions (VATS). Systematic implementation of specific measures in pre- (patient consulting before the intervention, compliance with fluid and nutrition regimen, exclusion of routine sedation, prophylaxis of venous thrombosis, use of intravenous antibiotics and alcohol skin-prepping solution with chlorohexidine), intra- (prevention of hypothermia, thoracoscopic approach, single-tube approach in anatomic lung resections, exclusion of pleural tube insertion, urethral catheterization for less than 2 hours and only in case of epidural anesthesia) and postoperative (early mobilization and cessation of intravenous infusion, pain control using combination of acetaminophen with NSAIDs, maintenance of normovolemy, use of balanced crystalloid solutions and non-pharmacological measures for nausea and vomiting control) periods promote improved outcomes, decrease of postoperative complication rate and postoperative mortality